EVEKTIVITAS FORUM MUSRENBANG DESA SEBAGAI REPRESENTASI WARGA DALAM PENYUSUNAN APBDES DI DESA HINGALAMAMENGI KABUPATEN LEMBATA - Sarabiti, Saire Rama; Helan, Yohanes Tuba; Asnawi, Norani (Petitum Law Journal, 2024)
Village Musrenbang is an aspiration space intended to accommodate community aspirations which are included in the Village Revenue and Expenditure Budget. In its implementation, it is only used as a formality in preparing the Village Revenue and Expenditure Budget. Many aspirations are only accommodated without being realized, such as in Hingalammengi Village, Omesuri District, Lembata Regency. The aim of this research is to determine the effectiveness of the implementation of Musrenbangdes and the factors that influence the implementation of the Musrenbangdes forum. This research uses descriptive empirical legal research methods, This research aims to provide input and add to the body of literature in the field of education, especially in the field of law. This research can also be used as a reference for readers and those who wish to continue further research. In the midst of the Village government's efforts to advance and prosper the Village, the Village government must provide space for the community to express their aspirations so that there is equality between the rights and obligations of both. In this case, the Musrenbangdes must be used as a transparent space to accommodate aspirations and can be included in the village revenue and expenditure budget.